Association between stroke knowledge, stroke awareness, and preventive behaviors among older people: A cross‐sectional study. (20th June 2019) - Pothiban, Linchong; Srirat, Chomphoonut
Abstract: In this cross‐sectional study, we compared preventive behaviors among Thai people aged> 60 years of age, with and without stroke risk, in Chiang Mai Province, Thailand, and examined the associations between stroke knowledge and stroke awareness with preventive behaviors in these two groups ( n = 422). Participants completed researcher‐developed tools, including the Personal Demographic Questionnaire, the Stroke Knowledge Questionnaire, the Awareness of Stroke Risk and Severity Questionnaire, and the Stroke Preventive Behavior Questionnaire. The findings revealed a significantly higher mean score of preventive behaviors in older people with stroke risk than in those without risk. For people with stroke risk, stroke knowledge did not result in a significant association with stroke‐preventive behaviors, while stroke awareness did. For those without stroke risk, both stroke knowledge and stroke awareness were significantly associated with stroke‐preventive behaviors. Although the stroke‐preventive behaviors of both groups were performed appropriately, it is necessary for people with stroke risk to maintain preventive behaviors, and for health professionals to regularly assess them for stroke symptoms and encourage people to be proactive about stroke‐preventive behaviors.